2012
DOI: 10.1186/1754-6834-5-71
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the caffeic acid O-methyltransferase gene in switchgrass reveals a novel monolignol analog

Abstract: BackgroundDown-regulation of the caffeic acid 3-O-methyltransferase EC 2.1.1.68 (COMT) gene in the lignin biosynthetic pathway of switchgrass (Panicum virgatum) resulted in cell walls of transgenic plants releasing more constituent sugars after pretreatment by dilute acid and treatment with glycosyl hydrolases from an added enzyme preparation and from Clostridium thermocellum. Fermentation of both wild-type and transgenic switchgrass after milder hot water pretreatment with no water washing showed that only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 52 publications
0
86
0
1
Order By: Relevance
“…Foracomprehensive discussion, the reader is referred to arecent review article. [11] Them ajority of phenylpropanoid genetic strategies have been directed towards ad ecrease in lignin content across plant species,w ith research relating to biomass conversion being targeted at hardwoods, [42][43][44] softwoods, [45] monocots (grasses), [46][47][48][49][50][51][52][53] and dicots (including Arabidopsis and alfalfa/ truncatula). [43, However,a ni ncrease in saccharification yield will not boost the economics of abiorefinery operation if the lignin fraction, at 15-30 wt %o fd ry biomass,b ecomes amore recalcitrant material.…”
Section: Bioengineering Of Ligninsmentioning
confidence: 99%
“…Foracomprehensive discussion, the reader is referred to arecent review article. [11] Them ajority of phenylpropanoid genetic strategies have been directed towards ad ecrease in lignin content across plant species,w ith research relating to biomass conversion being targeted at hardwoods, [42][43][44] softwoods, [45] monocots (grasses), [46][47][48][49][50][51][52][53] and dicots (including Arabidopsis and alfalfa/ truncatula). [43, However,a ni ncrease in saccharification yield will not boost the economics of abiorefinery operation if the lignin fraction, at 15-30 wt %o fd ry biomass,b ecomes amore recalcitrant material.…”
Section: Bioengineering Of Ligninsmentioning
confidence: 99%
“…One of the promising approaches for reducing biomass recalcitrance is the development of genetically engineered plants involving down-regulation/overexpression of key enzymes involved in lignin biosynthesis that can achieve an improved sugar release performance with reduced pretreatment severities (Li et al, 2003;Chen and Dixon, 2007;Weng et al, 2008;Pu et al, 2011b;Shen et al, 2012;Tschaplinski et al, 2012). A recent report by Shen et al (2012) has demonstrated that overexpression of PvMYB4 genes in switchgrass resulted in an approximately threefold increase in sugar release efficiency from transgenic cell wall residues.…”
Section: Introductionmentioning
confidence: 99%
“…Several novel monomers, all deriving from the monolignol biosynthetic pathway, have been found to incorporate into lignin in wild-type and transgenic plants. For example, monolignol acetate, p-hydroxybenzoate, and p-coumarate ester conjugates have all been shown to incorporate into lignin polymers and are the source of naturally acylated lignins (Ralph et al, 2004;Lu and Ralph, 2008); lignins derived solely from caffeyl alcohol were found in the seed coats of both monocot and dicot plants (Chen et al, 2012a(Chen et al, , 2012b; lignins derived solely from 5-hydroxyconiferyl alcohol were found in a cactus (for example, in a member of the genera Astrophytum) seed coat (Chen et al, 2012a); a Medicago truncatula transgenic deficient in cinnamyl alcohol dehydrogenase exhibited a lignin that was overwhelmingly derived from hydroxycinnamaldehydes (instead of their usual hydroxycinnamyl alcohol analogs; Zhao et al, 2013); and iso-sinapyl alcohol was implicated as a monomer in caffeic acid O-methyltransferase downregulated switchgrass (Panicum virgatum; Tschaplinski et al, 2012). These findings imply that plants are quite flexible in being able to use a variety of monomers during lignification to form the heterogenous lignin polymer.…”
mentioning
confidence: 99%